Solar radiation in Brazil: observations, historical simulations, projections and applications - Zuluaga Aristizábal, Cristian Felipe (2021)
Climate change is one of the greatest modern adaptation challenges facing humanity. Among the strategies to face this challenge is the use of renewable energies. The conversion of solar downward shortwave radiation (DSWR) to photovoltaic (PV) energy is considered a clean, sustainable and renewable energy technology that can help meet the energy demands of the growing world population, while reducing energy costs and the adverse human impacts of the use of fossil fuels. The main objective of this study is to evaluate the past and future changes in solar radiation in Brazil, and their consequences for the production of PV power potential (P PV ). Chapter 1 evaluates the spatiotemporal patterns of DSWR variability and trends in Brazil between 1980 and 2016, based on the most recent gridded datasets (observations, reanalysis and merging) and to explore the relationships between DSWR variability and decadal changes in cloud cover. The results showed that the ERA5 reanalysis delivered the DSWR values closest to the observations for all country regions. Also, DSWR shows a positive trend (“brightening”) for all of Brazil, particularly in the N, CW and SE regions. Strong correlations were found between cloud cover and observed DWSR, which indicated that the decadal changes in cloud cover are the main factor contributing to the “brightening” effect in Brazil. Chapter 2 evaluates how the CMIP6 models estimate the spatio-temporal variability of the DSWR and its causes in Brazil in the historical period 1981-2010. In addition, using an ensemble of the best models, it was estimated how the future changes (2021-2050 and 2071-2100) of DSWR, in two different scenarios of shared socioeconomic paths (SSP2-4.5 and SSP5-8.5), would affect the generation of photovoltaic systems in Brazilian territory. Future climate projections showed that P PV will have slight increases only in the north of the N region, south of the NE region, and in the SE region, under all scenarios and periods, with maximum growth values of 2.5% under SSP5-8.5 for the immediate future (2021 - 2050). Despite the greater availability of solar radiation, the sensitivity of current P PV systems’ technology to the increase in ambient temperature, would not allow increases in the yield of P PV . On the contrary, as the temperature increases, the efficiency of the solar panels decreases, canceling the positive effect of the increase in DSWR. Keywords: Solar radiation. CMIP6. Reanalyses. Climate changes. SSP